Magnetic resonance imaging and neuropsychological findings for predicting of cognitive deterioration in memory clinic patients - Matsuda, Kana; Shinohara, Masaki; Ii, Yuichiro; Tabei, Ken-ichi; Ueda, Yukito; Nakamura, Naoko; Hirata, Yoshinori; Ishikawa, Hidehiro; Matsuyama, Hirofumi; Matsuura, Keita; Satoh, Masayuki; Maeda, Masayuki; et al. (Frontiers in Aging Neuroscience, 2023)
Objective The severity of cerebral small vessel disease (SVD) on magnetic resonance imaging (MRI) has been assessed using hypertensive arteriopathy SVD and cerebral amyloid angiopathy (CAA)-SVD scores. In addition, we reported the modified CAA-SVD score including cortical microinfarcts and posterior dominant white matter hyperintensity. Each SVD score has been associated with cognitive function, but the longitudinal changes remain unclear. Therefore, this study prospectively examined the prognostic value of each SVD score, imaging findings of cerebral SVD, and neuropsychological assessment. Methods This study included 29 patients diagnosed with mild cognitive impairment or mild dementia at memory clinic in our hospital, who underwent clinical dementia rating (CDR) and brain MRI (3D-fluid attenuated inversion recovery, 3D-double inversion recovery, and susceptibility-weighted imaging) at baseline and 1 year later. Each SVD score and neuropsychological tests including the Mini-Mental State Examination, Japanese Raven’s Colored Progressive Matrices, Trail Making Test -A/-B, and the Rivermead Behavioral Memory Test were evaluated at baseline and 1 year later. Results Twenty patients had unchanged CDR (group A), while nine patients had worsened CDR (group B) after 1 year. At baseline, there was no significant difference in each SVD score; after 1 year, group B had significantly increased CAA-SVD and modified CAA-SVD scores. Group B also showed a significantly higher number of lobar microbleeds than group A at baseline. Furthermore, group B had significantly longer Japanese Raven’s Colored Progressive Matrices and Trail Making test-A times at baseline. After 1 year, group B had significantly lower Mini-Mental State Examination, Japanese Raven’s Colored Progressive Matrices, and Rivermead Behavioral Memory Test scores and significantly fewer word fluency (letters). Conclusion Patients with worsened CDR 1 year after had a higher number of lobar microbleeds and prolonged psychomotor speed at baseline. These findings may become predictors of cognitive deterioration in patients who visit memory clinics.